Quaternary deformation and fault structure in the Northern Mississippi Embayment as imaged by near‐surface seismic reflection data. Issue 5 (27th May 2014) - Guo, Lei; Magnani, Maria Beatrice; McIntosh, Kirk; Waldron, Brian
Abstract Seismicity in the New Madrid seismic zone (NMSZ) in the central United States constrains the location of present deformation at depth along four main distinct arms, while the surface expression of the ongoing deformation is still unclear. To better constrain the surface deformation in the NMSZ, we integrate existing seismic reflection data with a new ~300 km‐long high‐resolution seismic reflection profile acquired along the Mississippi River from Cape Girardeau, MO, to Caruthersville, MO. Based on the data, we interpret the Reelfoot Thrust and the New Markham Fault as upward splays of a blind master fault defined by the seismicity and extending at depth farther north. To the south, two faults, the Axial Fault and the Cottonwood Grove Fault, are imaged above the southern arm of the NMSZ. Both fault display deformation of the Paleozoic through the Tertiary sediments, and a relief of ~20–25 m at the base of the Quaternary alluvium, which we interpret as the result of strike‐slip motion along a complex fault plane geometry. We propose two alternative interpretations for the relationship between the shallow faults and the seismicity in this area: (1) the faults merge at depth and are presently both active and (2) the faults are distinct at depth and were active during the Quaternary and only the Axial Fault is presently deforming. Geological structures mapped at the surface as part of this study show that Quaternary deformation is accommodated along a fault network that is more complex than the simple four‐arm system illuminated by the seismicity, a behavior predicted by analog and computer models.